2022
DOI: 10.5620/eaht.2022002
|View full text |Cite
|
Sign up to set email alerts
|

Cardioprotective and antioxidant effects of taxifolin and vitamin C against diazinone-induced myocardial injury in rats

Abstract: In Iraq, excessive exposure to insecticides is increasingly becoming uncontrollable, the objective of this work was to assess the possible ameliorative role of taxifolin and vitamin c against diazinon-induced myocardial injury in rats. 36 sprague female rats divided into 6 groups of 6 rats each. Group 1 received diazinone 20 mg/kg gavaged for 30 days. Group 2 received taxifolin (25 mg/kg) and vitamin C (100 mg /kg) co-administered together and gavaged daily for 30 days before oral diazinone (20 mg/kg). Group 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…This was evidenced by considerably lower MDA, protein carbonyl, and NO levels, while elevating SOD, CAT, and GSH in cardiac tissues of mice pre-treated with TAX prior to ISO administration. In accordance with our results, several investigations have shown that the cardioprotective action of TAX is associated with reduced oxidative markers and elevated antioxidant components, resulting in ameliorated oxidative injury to the myocardium [ 39 , 40 , 49 ]. Furthermore, TAX exhibited tissue protective effect against chemically-induced oxidative damage in various experimental models, such as acrylamide-induced heart [ 21 ] and kidney injury [ 50 ], alcohol [ 25 ] and carbon tetrachloride (CCl 4 )-induced liver injury [ 25 ], and methanol-induced oxidative optic nerve damage [ 51 ].…”
Section: Discussionsupporting
confidence: 92%
“…This was evidenced by considerably lower MDA, protein carbonyl, and NO levels, while elevating SOD, CAT, and GSH in cardiac tissues of mice pre-treated with TAX prior to ISO administration. In accordance with our results, several investigations have shown that the cardioprotective action of TAX is associated with reduced oxidative markers and elevated antioxidant components, resulting in ameliorated oxidative injury to the myocardium [ 39 , 40 , 49 ]. Furthermore, TAX exhibited tissue protective effect against chemically-induced oxidative damage in various experimental models, such as acrylamide-induced heart [ 21 ] and kidney injury [ 50 ], alcohol [ 25 ] and carbon tetrachloride (CCl 4 )-induced liver injury [ 25 ], and methanol-induced oxidative optic nerve damage [ 51 ].…”
Section: Discussionsupporting
confidence: 92%
“…In addition, it has been proven to be effective in diabetic cardiomyopathy by inhibiting oxidative stress to regulate mitochondrial function and inhibit cell apoptosis ( Sun et al, 2014 ; Zheng et al, 2021 ). Moreover, taxifolin exerts cardioprotective effects against diazinon-induced myocardial injury in rats ( Najeb et al, 2022 ). However, it has been reported that taxifolin aglycone is found in complex preparations such as silymarin (LegalonTM), is presented in very small amounts, and is rarely used alone ( Kroll et al, 2007 ; Weidmann, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…(8,12) It is one of more than 4000 plant phenolics that are naturally available, (13) in many vegetables, fruits and drinks ingested from the daily diet, (14) including onions, broccoli, apples, berries, (15) and citrus fruits, (9) it is ubiquitously present in wine and tea. (16,17) Que is well known for its vasodilator, antihypertensive effects, antiatherosclerotic, antiobesity, antihypercholesterolemic, and antidiabetic activities. (18)(19)(20) Que's mechanisms of action are pleiotropic, involves the decrease of glucose absorption from the intestine, insulin secretory and insulin-sensitizing effects, and the enhancement of glucose uptake in the muscles.…”
Section: Introductionmentioning
confidence: 99%